Toward consilience in reptile phylogeny: miRNAs support an archosaur, not lepidosaur, affinity for turtles. Issue 4 (5th May 2014) - Field, Daniel J.; Gauthier, Jacques A.; King, Benjamin L.; Pisani, Davide; Lyson, Tyler R.; Peterson, Kevin J.
SUMMARY Understanding the phylogenetic position of crown turtles (Testudines) among amniotes has been a source of particular contention. Recent morphological analyses suggest that turtles are sister to all other reptiles, whereas the vast majority of gene sequence analyses support turtles as being inside Diapsida, and usually as sister to crown Archosauria (birds and crocodilians). Previously, a study using microRNAs (miRNAs) placed turtles inside diapsids, but as sister to lepidosaurs (lizards and Sphenodon) rather than archosaurs. Here, we test this hypothesis with an expanded miRNA presence/absence dataset, and employ more rigorous criteria for miRNA annotation. Significantly, we find no support for a turtle + lepidosaur sister‐relationship; instead, we recover strong support for turtles sharing a more recent common ancestor with archosaurs. We further test this result by analyzing a super‐alignment of precursor miRNA sequences for every miRNA inferred to have been present in the most recent common ancestor of tetrapods. This analysis yields a topology that is fully congruent with our presence/absence analysis; our results are therefore in accordance with most gene sequence studies, providing strong, consilient molecular evidence from diverse independent datasets regarding the phylogenetic position of turtles.